ALPHAMETHRIN TOXICITY: EFFECT ON THE REPRODUCTIVE ABILITY AND THE ACTIVITIES OF PHOSPHATASES IN THE TISSUES OF ZEBRAFISH, DANIO RERIO: Life Science-Toxicology - ANSARI, SHABNAM; ALAM ANSARI, BADRE (International Journal of Life Science and Pharma Research, 2012)
Alphamethrin, a synthetic pyrethroid used extensively for the control of insect pests and public health programmes. In the present study, the adult Zebrafish, their embryos and fingerlings were used as a model to investigate the toxic effects of Alphamethrin. The 24 to 96-h LC10, LC50 and LC90, slope and chi-square values were calculated for the adults and fingerlings exposed to Alphamethrin. The 24-h LC50 value of Alphamethrin was 1.29 μg l-1 and for 96-h 0.17 μg l-1 for adults. The 72-h LC50 for the embryo was 0.024 μg l-1 and for fingerlings the 96-h LC50 value of Alphamethrin was 0.020 μg l-1. The results show significant decrease in fecundity and hatchability in comparison to the control group. The present study was also aimed to investigate the changes in the activities of enzymes acid phosphatase (ACP) and alkaline phosphatase (ALP) in the gill and liver of Zebrafish after exposure to 20 %, 40 %, 60 % and 80 % of the 24-h LC50 values of Alphamethrin. It was found that the activities of ACP and ALP in treated fishes were significantly reduced (p < 0.05) in response to treatment of pesticide as compared to control. The toxicity was concentration as well as time dependent.